Management of water resources in protected areas - Corvea Porras, José Luis; de Bustamente Gutiérrez, Irene; LaMoreaux, James W.; Farfan Gonzalez, Hermes (Environmental Earth Sciences, 2013)
Natural ecosystems are heavily dependent on water, as it is essential to the development of life. The ecology and landscape play an important role in the quality and availability of water. It is no coincidence that exceptional hydrological phenomena are found in protected areas. Such is the case with, for example, the geothermic occurrences (principally, geysers) in America's Yellowstone National Park , the oldest park in the world. The Ramsar wetlands (where the ecosystem's dependency on water is strongly evident), The Iguaçu Falls (on the border of Argentina and Brazil), or the Zapata Swamp (the largest of its kind on the Caribbean island of Cuba) further exemplify this point. However, in many cases, the conservation strategies for hydraulic resources in protected areas are ignored, or simply deprived of the attention they require. There are many types of suitable management strategies for planning and protecting our valuable treasures. Hydraulic resource management in protected areas is something that must not be separated from these conservation measures. The first Symposium for the Management of Hydraulic Resources in Protected Areas was intended to be a framework of communication about experiences with water resource management in protected areas. Advances in research and possible solutions to the problems within these areas were discussed. The contributions in this proceedings volume are grouped under seven main themes: Purification and reuse of wastewater in rural communities; Impact of public use on water resources; Vulnerability and risks associated with aquifers, Design and management water resources in protected areas; Research and monitoring of water resources in protected areas; Water and its importance as a source of renewable energy in protected spaces; and Geodiversity and conservation of areas with hydraulic heritage.